Diaphragm Ultrasound: A Valuable Predictor of the Outcome of Extubation. An Observational Pilot Study in Covid-19 Related ARDS - Gagliardi, Veronica; Butturini, Angelo; Ferraro, Gioconda; Gagliardi, Giuseppe (Archives of Clinical and Biomedical Research, 2022)
Introduction: Because both early and delayed weaning are associated with increased mortality, longer stay in the ICU and higher economic costs, performing extubation once the patient can cope with the respiratory load is completely recommended. Ultrasound Sonography (US) is an available bedside tool that allows a rapid assessment and visualization of the different structures involved in spontaneous breath. M-mode ultrasonography can be useful for the assessment of diaphragm kinetics, providing valuable information about diaphragm disfunction. Aim of the Study: The aim of this study is to find a correlation between the value of the acceleration of the diaphragm detected with the US M-mode and the outcome of the weaning. Materials and Methods: We have enrolled 19 patients admitted in our ICU. Each patient underwent the trial with the ultrasound M-mode to assess the acceleration of the diaphragm during the contraction. We have analyzed the results relating them to the outcome of the weaning. Results: While 11 of our patients have had a successful weaning, 8 have failed it, and we can see that the outcome is associated to the values of acceleration. Discussion: Our study has demonstrated that an assessment of the diaphragm function using US could represent a usable and effective technique as the acceleration is related to the force generated by the diaphragm contraction. Conclusions: In conclusion, the acceleration could be a useful parameter to consider when it comes to the prediction of the outcome of the weaning process.